50th Anniversary Article: The Evolution of Research on Information Systems: A Fiftieth-Year Survey of the Literature in Management Science - Banker, Rajiv D.; Kauffman, Robert J. (Management Science, 2004)
The development of the information systems (IS) literature in Management Science during the past 50 years reflects the inception, growth, and maturation of several different research streams. The five research streams we identify incorporate different definitions of the managerial problems that relate to IS, the alternate theoretical perspectives and different methodological paradigms to study them, and the levels of the organization at which their primary results impact managerial practice. The decision support and design science research stream studies the application of computers in decision support, control, and managerial decision making. The value of information research stream reflects relationships established based on economic analysis of information as a commodity in the management of the firm. The human-computer systems design research stream emphasizes the cognitive basis for effective systems design. The IS organization and strategy research stream focuses the level of analysis on the locus of value of the IS investment instead of on the perceptions of a system or its user. The economics of information systems and technology research stream emphasizes the application of theoretical perspectives and methods from analytical and empirical economics to managerial problems involving IS and information technologies (IT). Based on a discussion of these streams, we evaluate the IS literature's core contributions to theoretical and managerial knowledge, and make some predictions about the road that lies ahead for IS researchers.